Las nuevas derechas en el escenario electoral de México, 2024 - Campos López, Xóchitl Patricia (2024)
In Mexico, the right has developed under the influence of traditional conservatism from Spain and the United States. The 2018 electoral process elevated a party identified with progressivism and, although its government cannot be considered extreme left, it has tried to confront the neoliberal order. The above forced the previously competitive parties to seek winning alliances, even if this was their ideological identity. This is what happened with the National Action Party, classified as the party of the traditional Mexican, Hispanicist right that, in the face of the confusion of a sector of its captive electorate, stars in a paradoxical electoral alliance.At the same time that the representation of this conservative electorate was in danger, new actors appeared raising anti-communist, anti-progressive rhetoric, which also denounced the government's inability to confront insecurity, which accused an insufficient welfare state or proposed the privatization of assets. and services. These actors, who confront not only the current government but also the traditional right. They propose, at the same time, a mix of Christian values, Catholic symbols and a close relationship with the United States.